THE INFLUENCE OF THE WORLD'S FOOD TRADITIONS ON ATHEROSCLEROSIS REVIEW (Web of Teachers: Inderscience Research, 2024)
The authors gave a review of current literature on the impact of food traditions of the world on the development of atherosclerosis. Analytical information on modern trends in the transformation of culinary preferences is presented. It was found that in the conditions of today's globalization and unification, among representatives of the older generation, food remains as a stable marker of ethnic identity. On the other hand, the younger generation is largely committed to unification, which is manifested in the consumption of store-bought products, dishes based on recipes from the Internet, not to mention fast food, which has a single standard throughout the world. An analysis of literature from open sources of the last 5 years on the influence of ethnic food traditions on the development of atherosclerosis was performed. Deviations in eating habits are indicated, accompanied by appetite disturbances and obesity, which is important in the development of atherosclerosis. An obvious dependence of life expectancy on dietary style has been demonstrated. Examples such as the Mediterranean diet and traditional nutrition in Japan have shown beneficial effects on atherosclerosis. Explanation of the possible mechanisms of this phenomenon is the essence of this work.